2016
DOI: 10.1186/s12879-016-1912-5
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus aureus bacteremia with iliac artery endarteritis in a patient receiving ustekinumab

Abstract: BackgroundUstekinumab (Stelara®), a human monoclonal antibody targeting the p40-subunit of interleukin (IL)-12 and IL-23, is indicated for moderate to severe plaque psoriasis and psoriatic arthritis. In large multicenter, prospective trials assessing efficacy and safety of ustekinumab increased rates of severe infections have not been observed so far.Case presentationHere, we report the case of a 64-year old woman presenting with chills, pain and swelling of her right foot with dark maculae at the sole, and el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
0
4
0
1
Order By: Relevance
“…To date, clinical trials have not reported an increased risk of bacterial skin infections in secukinumab and ustekinumab users ( 27 , 28 ). A single case report has described the occurrence of S. aureus bacteraemia with iliac artery endarteritis after the third dose of ustekinumab ( 14 ). Only a few case reports have been published on bacterial skin infections during TNF-α inhibitor therapy ( 29 , 30 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, clinical trials have not reported an increased risk of bacterial skin infections in secukinumab and ustekinumab users ( 27 , 28 ). A single case report has described the occurrence of S. aureus bacteraemia with iliac artery endarteritis after the third dose of ustekinumab ( 14 ). Only a few case reports have been published on bacterial skin infections during TNF-α inhibitor therapy ( 29 , 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…For ustekinumab, multiple cases of bacterial skin infections and Herpesviridae infections have been described in clinical trials and case reports (13)(14)(15). Herpesviridae infections were seen more frequently during the first 12 weeks of treatment with secukinumab compared with etanercept (16).…”
mentioning
confidence: 99%
“…Во время стафилококковой инфекции интерлей-кин 1β (interleukin-1β -IL-1β) в основном способ-ствует привлечению нейтрофилов в очаг поражения [19,48]. Интерлейкин IL-1β, взаимодействуя с ре-цептором IL-1R многочисленных типов иммуно-цитов, активирует внутриклеточный MyD88/IRAK/ …”
Section: Il-1βunclassified
“…The levels of these cytokines, along with others derived from TH 17 cells, in skin lesions as well as in peripheral blood have been shown to be elevated in psoriasis patients as compared to their healthy counterparts [ 5 ]. IL-17 has also been shown to act on dermal fibroblasts in stromal tissue leading to the production of pro-inflammatory cytokines that promote the expression of keratin 17, which is the only keratin that has been found in the lesions of psoriasis patients [ 6 ].…”
Section: Introductionmentioning
confidence: 99%